A simple estimate for the social cost of carbon. (October 2018) - Zhen, Zaili; Tian, Lixin; Ye, Qian
Abstract: The social cost of carbon plays an important role in environmental policy, which is the marginal external cost caused by the increase of carbon dioxide emissions. Calculating the social cost of carbon is to measure the externality of the carbon, which has a great significance for climate policy formulation. We bring the accumulated knowledge in climate research to the field of analytical economics. Different from the methods of Integrated Assessment Methods (IAMs), based on marginal cost method, a simple formula to determine the social cost of carbon is established.